Loans and Advances Portfolio Mix of Public Sector Development Banks in Bangladesh - Rabiul Alam, S. M.; Hossain, Syed Zabid (Indian Journal of Finance, 2012)
The portfolio management of public sector development banks in Bangladesh was very inefficient during 1999-2009. The cotton, wool and synthetics textile sector in BSB and jute and allied sector in BSRS occupied a lion's share of the portfolio of loan and advances during the period. All other sectors collectively occupied a very small share of their loan and advance portfolio, and as such, they had measurably failed to diversify their risk in different economic activities. More revealing is that the absolute amount of loans and advances had a declining trend. Contrarily, classified loan and advances dominated the structure of loan and advances during the whole period of review. Bad debt alone was the major contributor of classified loss as against substandard and doubtful debt.